Toddlers at Elevated Likelihood for Autism: Exploring Sensory and Language Treatment Predictors. (March 2023) - Jatkar, Alapika; Garrido, Dunia; Zheng, Shuting; Silverman, Greyson; Elsayed, Heba; Huguely Davis, Paige; Lee, Helen; Crais, Elizabeth R.; Sideris, John; Turner-Brown, Lauren; Baranek, Grace T.; Watson, Linda R.; et al.
Baseline child characteristics may predict treatment outcomes in children with or at elevated likelihood of developing autism (EL-ASD). Little is known about the role of child sensory and language features on treatment outcome. Participants were randomly assigned to a parent-mediated intervention or control condition. Analyses explored the relationship between baseline child sensory and language characteristics and changes in ASD symptoms over approximately 9 months. Higher baseline sensory hyporeactivity was significantly related to less improvement in social communication (SC) for the treatment group only. More baseline atypical vocalizations were significantly related to less improvement on SC across treatment and control groups. This work provides an initial framework to encourage the tailoring of interventions for EL-ASD children, suggesting sensory reactivity and atypical vocalizations may be useful behaviors to consider in treatment planning.